2023
DOI: 10.3390/gels9050426
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Radiation-Induced Advanced 2,3-Dimethylacrylic Acid-(2-Acrylamido-2-methyl-1-propanesulfonic Acid) Superabsorbent Hydrogel: Synthesis and Characterization

Abstract: Gamma radiation technique for the preparation of pure hydrogels is gaining popularity worldwide. Superabsorbent hydrogels play vital roles in different fields of application. The present work mainly focuses on the preparation and characterization of 2,3-Dimethylacrylic acid-(2-Acrylamido-2-methyl-1-propane sulfonic acid) (DMAA–AMPSA) superabsorbent hydrogel by applying gamma radiation and optimization of the proper dose. To prepare DMAA–AMPSA hydrogel, different doses ranging from 2 kGy to 30 kGy were imparted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…After polymerization, a monolithic sample with high crosslinking was directly obtained by venting CO 2 ( Figure 1 b). When the sample was immersed in water, its original shape was still retained and achieved an opaque state, as depicted in Figure 2 g. Therefore, the porous hydrogel prepared through the present route was very different from those formed via the conventional synthesized method [ 19 ]. In particular, the gel was soft and dimensionally stable in this studied case.…”
Section: Resultsmentioning
confidence: 93%
“…After polymerization, a monolithic sample with high crosslinking was directly obtained by venting CO 2 ( Figure 1 b). When the sample was immersed in water, its original shape was still retained and achieved an opaque state, as depicted in Figure 2 g. Therefore, the porous hydrogel prepared through the present route was very different from those formed via the conventional synthesized method [ 19 ]. In particular, the gel was soft and dimensionally stable in this studied case.…”
Section: Resultsmentioning
confidence: 93%
“…Such hydrogels exhibit outstanding performance in dye adsorption, positioning them as viable candidates for eco-friendly water purification methods. This methodology capitalizes on gamma radiation’s crosslinking strengths alongside the inherent polysaccharide framework of potato starch, further augmented by acrylic acid, to effectively purify water by eliminating pollutants [ 66 , 67 , 68 ].…”
Section: Synthesis and Properties Of Hydrogelsmentioning
confidence: 99%
“…The gel shows peaks at 0.88 and 1.23 for methyl (-CH 3 -) protons (carbon no. 1,2,19,20). The peak at 2.62 is for -CH-protons (carbon no.…”
Section: The Characterization Of Gel Using Proton Nmr Spectroscopymentioning
confidence: 99%
“…Due to the lack of use of initiators and cross-linking agents, among all of the methods, the gamma radiation technique is the most promising, effective, and prioritized for the preparation of pure gel. Gamma radiation is a highly energetic (<0.25 Å wavelength, >12 EHz (1 EHz = 10 18 Hz) and >50 keV energy) electromagnetic ray that can initiate copolymerization in both aqueous and non-aqueous solutions [ 17 , 20 ]. However, a detailed study regarding DMAA-DAM gels in non-aqueous solutions was not yet reported.…”
Section: Introductionmentioning
confidence: 99%